Narcissism and social media addiction: gender, social demographics, and social media use - Syahputra, Yuda; Ifdil, Ifdil; Hafni, Merri; Solihatun, Solihatun; Oktara, Tri Windi; Erwinda, Lira (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
This study aims to describe differences in narcissism and social media addiction based on gender, social demographics, and use of social media. This research is a comparative student, the sample for this study amounted to 123 students in Vocational High School (SMK) in DKI Jakarta. There are two instruments used in this study, namely, the narcissistic instrument (22 items) and the social media addiction instrument (17 items). Data were analyzed using descriptive analysis and Multivariate One-Way Analysis of Variance Model (MANOVA). The findings for this study indicate that there are significant differences in narcissistic and social media addiction variables based on gender, number of social media accounts, and gender-daily internet access. In addition, there is a significant difference in social media addiction based on domicile. Gender and the order of children in the family are also significantly different on the variables of social media addiction. Based on the results of this study, it is hoped that further researchers will link other variables (for example: self-esteem, loneliness, subjective well-being, stress, etc.) to prevent narcissistic behavior and social media addiction in education.